Static and dynamic balance in young athletes - Ricotti, L. (Journal of Human Sport & Exercise, 2011)
The creation of a mature athlete necessarily passes through the expression of his potential during each phase of his development. Young athletes' trainers often neglect specific balance programs, above all in certain sports (e.g. soccer) where balance is poorly considered, but that is fundamental for the execution of complex technical movements, as well as for the prevention of future injuries. In this paper we highlight that balance training at specific ages is important for the maturation of the sensorimotor abilities that are important for a high level athlete. We discuss the main methods used to assess balance in sports, including some useful formulae that can be used to quantify postural performances, and we report the major findings concerning static and dynamic analyses on children and adolescents. Finally, we discuss the existing literature regarding balance recordings on adults, adolescents and children involved in one or more sport activities at regional, national or international level, highlighting the need of further research on the mechanisms underlying balance improvements related to different sport activities at various ages.